IMPACT ATTENUATION OF PROTECTIVE BOXING AND TAEKWONDO HEADGEAR. Issue 7 (11th March 2014) - O'Sullivan, D; Fife, G; Pieter, W
Abstract : Background: To date, only one study reported the impact attenuation of protective taekwondo headgear. Although Olympic boxing has discontinued the use of headgear, similarities in designs are thought to provide a framework for improvements of taekwondo headgear. Objective: To determine differences in impact attenuation of taekwondo and boxing headgear. Design: Between groups. Setting: Impact biomechanics laboratory. Participants: World Taekwondo Federation (WTF) and Amateur International Boxing Association (AIBA) approved protective headgear. Risk factor assessment: A standardized (ASTM F-2397) martial arts headgear striker was used to impart impacts to a 50th Percentile Male Hybrid III Dummy head and neck complex. All impacts were imparted with a terminal striking velocity of 5.0 m/s (min - max=4.75 −5.15m/s). 2 AIBA-approved headgear (Adidas and Green Hills) and 2 WTF-approved headgear were selected for testing. Each headgear model was fitted to the Hybrid III and impacted a total of 5 times to the left side (temporal) of the headgear along an ASTM-specified impact region. As per ASTM standards low velocity impacts must yield head RLAs below 50g. Main outcome measurements: Resultant linear acceleration (RLA). Results: 1-way ANOVA showed significant differences between the headgear brands (eta 2 =0.928). The most protection was provided by the taekwondo Adidas headgear (60.5±4.3g) followed by the boxing Adidas (75.4±9.9g), boxing Greenhill (109.4±10.11g), and taekwondo Nike headgear (129.5±8.2g). The greatest difference in RLA was observed between the two taekwondo models (d=−9.54, 95% CI=−13.91 – −5.18), whereas the smallest clinically meaningful difference was observed between the two Adidas models (d=−1.94, 95% CI=−3.20 – −0.29). Conclusions: Each of the headgear brands performed differently under the testing conditions. All models need to be redesigned to mitigate low velocity impacts. Future testing must include impacts at high impact velocities.